RELIGIOUS ETHICS FOR APPRECIATING CULTURAL DIVERSITY - Mohammad Ismath Ramzy; Md Saad , Rahimi; Sulaiman, Abdul Muhsien (Journal of Dharma, 2022)
Appreciating cultural diversity is the seventh target of Quality Education (SDG 4). Although connections worldwide are increasing, cultural diversity among people has become challenging. Islam sees cultural disparity as natural; al-’adl (non-bias), the central concept of Islamic ethics not only promotes cultural appreciation but makes it compulsory for just leadership. This research explores the association between al-’adl and cultural appreciation in Islamic religious texts and its implication in history. The objective of this research is to highlight the obligatory stance of Islam on cultural diversity appreciation in a multicultural context. The researchers recommend that Islamic religious leaders and religious institutions promote cultural appreciation as a fundamental obligation to ensure justice (al-’adl) in a society.